Sequence-controlled molecular layers on surfaces by thiol–ene chemistry: synthesis and multitechnique characterization. Issue 38 (14th September 2017) - Llevot, A.; Steinmüller, S. O.; Bitterer, B.; Ridder, B.; Berson, J.; Walheim, S.; Schimmel, T.; Bräse, S.; Scheiba, F.; Meier, M. A. R.
Abstract : Silicon surfaces were functionalized by thiol–ene chemistry using sequential reactions of different α, ω-dienes and α, ω-dithiols bearing marker moieties. Abstract : Silicon surfaces were functionalized by thiol–ene chemistry using sequential reactions of different α, ω-dienes and α, ω-dithiols bearing marker moieties. A system of six individual layers was achieved and exhaustively characterized by combining independent techniques such as X-ray Photoelectron Spectroscopy, Time-of-Flight Secondary Ion Mass Spectrometry and Atomic Force Microscopy using a molecular ruler system.